FAMILY LIVES. ASPECTS OF LIFE AND DEATH IN ANCIENT FAMILIES - Denisa Murzea (Journal of Ancient History and Archaeology, 2019)
Kristine Bøggild Johannsen, Jane Hjarl Petersen (eds.), FAMILY LIVES. ASPECTS OF LIFE AND DEATH IN ANCIENT FAMILIES (Acta Hyperborea 15), Copenhagen: Museum Tusculanum Press, 2019, 341 pages. ISBN: 9788763546393